2015
DOI: 10.1161/circheartfailure.114.001879
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Socioeconomic Status in Predicting 30-Day Outcomes After Heart Failure Hospitalization

Abstract: Background An individual's socioeconomic status (SES) is associated with health outcomes and mortality, yet it is unknown whether accounting for SES can improve risk-adjustment models for 30-day outcomes among Centers for Medicare & Medicaid Services (CMS) beneficiaries hospitalized with heart failure (HF). Methods and Results We linked clinical data on hospitalized HF patients in the Get With The Guidelines®-HF™ database (01/2005–12/2011) with CMS claims and county-level SES data from the 2012 Area Health R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 32 publications
2
39
0
1
Order By: Relevance
“…43 However, a similar study using data from GWTG-HF linked to Medicare claims and more aggregate county-level data on socioeconomic status found more modest associations between county-level socioeconomic status and 30-day outcomes. 44 Taken together, these 2 studies suggest that the local environment probably plays a role in readmissions, but a more detailed understanding of the community may be important.…”
Section: Consider the Environmentmentioning
confidence: 96%
“…43 However, a similar study using data from GWTG-HF linked to Medicare claims and more aggregate county-level data on socioeconomic status found more modest associations between county-level socioeconomic status and 30-day outcomes. 44 Taken together, these 2 studies suggest that the local environment probably plays a role in readmissions, but a more detailed understanding of the community may be important.…”
Section: Consider the Environmentmentioning
confidence: 96%
“…HCUP includes acute care hospital data in the United States, with all-payer (source of payment for the hospital length of stay). This database has all-payer data on hospital inpatient stays from selected states, however only few studies have focused on CHF and AD, hospital characteristics and reported studies are mainly on cost effectiveness [12][13][14] with few in longitudinal and population based studies [15].…”
Section: Research Designs and Methodsmentioning
confidence: 99%
“…Asians had similar rates with whites. However, when SES is included in the model, Hispanics and African Americans had modestly lower 30-day and 1-year mortality rates than Whites, but there were similar 30-day re-hospitalization rates among these ethnic groups [12,13]. A recent randomized trial of 2331 patients, with CHF and an ejection fraction (EF) ≤ 35 showed that compared to Whites, African-Americans patients (N=749) tended to be younger, had lower SES, higher rates of hypertension and diabetes with less ischemic etiology [8].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…6 An additional recommendation is particularly relevant to this discussion: "NQF and others … should develop strategies to identify a standard set of sociodemographic variables (patient and community-level) to be collected and made available for performance measurement and identifying disparities." 6 In this issue of Circulation: Heart Failure, Eapen et al 7 add to the body of literature on the relationship between socioeconomic variables and heart failure outcomes in a way that helps us understand how a standard set of socioeconomic variables should be collected. They used patient and hospital characteristics obtained from the well-known Get With The Guidelines-Heart Failure program to develop prediction models for 30-day readmission and mortality rates obtained from Medicare claims, compared predictions from the models with actual rates, then used Census data to assess the value of adding socioeconomic variables to the prediction models.…”
Section: Article See P 473mentioning
confidence: 99%